Estimation of the Tourism Crisis in Ecuador by COVID-19 with a View to a Post-Pandemic Reactivation - HERRERA, Diego BRAZALES (The journal of contemporary issues in business and government, 2021)
This research refers to how fragile the tourism economy of Ecuador is due to the effects of the appearance of COVID-19, which is why it is proposed to estimate the context of the country’s tourism crisis at the time of the coronavirus in 2020. The scope of the research is descriptive, with a quantitative, comparative, cross-sectional approach with the use of descriptive figures and bibliographic sources. A general breakdown of tourism in Ecuador in 2020 with a drop in GDP of -11%, an increase in unemployment by 6.6%, more than 1.2 billion USD in losses and a general breakdown of tourism companies, in addition to the contraction of prices of the sector of -20.20%, with a GVA rate of -18.3% in food and beverage companies, and finally tourism consumption was -0.065%, evidenced by a 98.4% reduction in tourism income international, determining a cautious forecast of the reactivation of tourism to the year 2026 based on GDP projections. This research contributes to the scientific knowledge of the economic tourism phenomenon of Ecuador and will be used by universities, professors, students and the private sector.